CLASSIFYING CYBERCRIME NETWORKS: ORGANIZED AND TRANSNATIONAL SCHEMES IN THE DIGITAL ERA - Tiutiunyk, Inna; Toptunenko, Dmytro; Flaumer, Anna (Socio-economic relations in the digital society, 2024)
The purpose of this study is to analyze and classify the main schemes of organized and transnational cybercriminal activity, as well as to identify the methods and technologies used by cybercriminals to carry out criminal activities in the digital space. The article explores current trends in cybercrime, such as the rise in financial fraud, ransomware attacks, phishing, and DDoS attacks. The study shows that the use of the latest technologies, particularly cryptocurrencies and the Internet of Things (IoT), significantly complicates the detection and prosecution of cyber criminals, necessitating the constant improvement of legal and technical tools to combat cybercrime. Key findings indicate that the transnational nature of cybercrime often makes it difficult to prosecute criminals across jurisdictions, requiring greater international coordination. It was also found that cybercriminals are using increasingly sophisticated methods to conceal their activities, incorporating modern technological solutions into criminal schemes. This underscores the need for continuous monitoring of new threats and the updating of protection methods for both organizations and individual users. The main conclusions of the study emphasize the importance of global cooperation in the fight against cybercrime, the need to enhance technological protection, and the development of legal mechanisms to counter modern cyber threats.
Keywords: organized and transnational cybercrime; financial fraud; ransomware attacks; phishing; DDoS attacks